Relationship Between High-Sensitivity C-Reactive Protein and Long-Term Outcomes in Elderly Patients With 3-Vessel Disease. (January 2022) - Liu, Yue; Zhang, Ce; Jiang, Lin; Xu, Lianjun; Tian, Jian; Zhao, Xueyan; Feng, Xinxing; Wang, Dong; Zhang, Yin; Sun, Kai; Xu, Jingjing; Liu, Ru; et al.
The prognostic value of high-sensitivity C-reactive protein (hsCRP) in complex coronary artery disease has not been fully established. We aimed to determine the association between hsCRP and long-term outcomes in elderly patients with 3-vessel disease (TVD). From April 2004 to February 2011, 3069 patients aged ≥65 years with TVD were consecutively enrolled and received medical treatment alone, percutaneous coronary intervention, or coronary artery bypass grafting. The patients were divided into 2 groups according to their hsCRP levels: <3.00 mg/L (62.1%) and ≥3.00 mg/L (37.9%). The mean age was 71 ± 4 years. The high hsCRP group had more risk factors and more frequently received conservative treatment than the low hsCRP group. During a median follow-up period of 6.2 years, elevated hsCRP was significantly associated with increased all-cause death (19.5% vs 29.6%, P < .001), cardiac death (9.4% vs 15.2%, P = .001), and major adverse cardiovascular and cerebrovascular events (34.1% vs 42.5%, P = .001). Multivariable Cox regression analyses revealed that hsCRP was an independent predictor for all of these events. Combining hsCRP with Synergy between PCI with TAXUS and Cardiac Surgery score II further improved the predictive power of the score. The relationship between hsCRP and mortality was relatively consistent across subgroups. Overall, hsCRP could prove useful for risk prediction in elderly patients.